ALTERNATIVE ASSESSMENT METHODS IN EVALUATION FUTURE FOREIGN LANGUAGE TEACHERS’ LEARNING ACHIEVEMENTS - Panchenko, Violetta Volodymyrivna (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. Major changes happening in the national system of foreign languages teaching in the context of the Bologna Process lead to the appearance of new strategies, updating of the educational contents, methods and techniques. Nowadays most educators realize that standard assessment approaches do not correspond to the evaluation goals of all the skills which are significant in modern professional life. Therefore, their attention shifts to alternative assessment techniques. Purpose. The aim of the article is to analyze different formats of alternative assessments used in foreign language teaching. Results. Alternative assessments are an important means of gaining a dynamic picture of students’ academic and linguistic development. Alternative assessment refers to procedures and techniques which can be used within the context of instruction and can be easily incorporated into the daily activities of the group. It is particularly useful with English as a second language students because it employs strategies that ask students to show what they can do. In contrast to traditional testing, students are evaluated on what they integrate and produce rather than on what they are able to recall and reproduce. Although there is no single definition of alternative assessment, the main goal is to gather evidence about how students are approaching, processing, and completing real-life tasks in a particular domain. Alternative assessment includes a variety of methods that can be adapted for different situations. Among the most popular formats are authentic assessment, assessment rubrics (holistic, analytic, primary trait, multitrait), role plays, reading response logs, dialogue journals, portfolio, checklists. The main advantage of alternative assessments methods is their ability to assess students’ proficiency in performing complex tasks that are directly associated with learning outcomes. Originality. The most popular alternative assessment methods are thoroughly analyzed, the significance of their usage in the professional training of future foreign language teachers is stressed. Conclusion. Combined with traditional forms of assessment, alternative assessment gives a more comprehensive and complete look at a student’s progress. Although the challenge to modify existing methods of assessment and to develop new approaches is not an easy one, the benefits for both teachers and students are great. The ideas and models presented here are intended to be adaptable, practical, and realistic for teachers who are dedicated to creating meaningful and effective assessment experiences for English as a second language.